Film and television analysis : an introduction to methods, theories, and approaches - Benshoff, Harry M., 1963- (Routledge, Taylor & Francis Group, 2016)
"Film and Television Analysis is especially designed to introduce undergraduate students to the most important qualitative methodologies used to study film and television. The methodologies covered include: * ideological analysis * auteur theory * genre theory * semiotics and structuralism * psychoanalysis and apparatus theory * feminism * postmodernism * cultural studies (including reception and audience studies) * contemporary approaches to race, nation, gender, and sexuality. With each chapter focusing on a distinct methodology, students are introduced to the historical developments of each approach, along with its vocabulary, significant scholars, key concepts and case studies. Other features include: * Over 120 color images throughout * Questions for discussion at the end of each chapter * Suggestions for further reading * A glossary of key terms. Written in a reader-friendly manner Film and Television Analysis is a vital textbook for students encountering these concepts for the first time."--Resumé vydavatele
Terminologický slovník
Keywords: filmová kritika; televizní kritika; filmová teorie; sociologie filmu; film criticism; television criticism; theory of film; učebnice; textbooks